Penerapan Metode Jigsaw Learning dalam Pembelajaran Pendidikan Agama Islam di SMP 3 Sendana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the application of the Jigsaw Learning method in Islamic Religious Education (PAI) learning at SMP 3 Sendana and to identify the advantages and obstacles encountered during the learning process. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the Jigsaw Learning method can increase student activeness, strengthen group cooperation, and help understand the material more deeply and comprehensively. In this activity, students not only act as recipients of information from the teacher, but also as conveyors of material to their group mates. The process of sharing information between members encourages students to be more active in seeking out, understanding, and explaining the concepts being studied. In addition, this method also creates a collaborative and enjoyable learning atmosphere, due to the positive social interactions between students. This can increase a sense of responsibility and concern for the success of the group. However, in its implementation, several obstacles were found that require attention. Some of these include limited study time within the available lesson hours, inequality in contributions between group members which sometimes results in an uneven workload, and a lack of student readiness to understand the material independently before the group discussion process takes place. Despite the challenges, these obstacles can be minimized through effective classroom management, such as balanced group division, motivation, and intensive teacher support throughout the learning process. With the right strategy, Jigsaw Learning remains an effective and relevant method for Islamic Religious Education (PAI) learning, as it encourages the achievement of learning objectives in a participatory, active, and enjoyable manner. Therefore, this method is a worthy alternative to cooperative learning that can improve the quality of religious education at the junior high school level.